Comparative analysis of short-term efficacy between robot-assisted retrograde drilling and arthroscopic microfracture for osteochondral lesions of the talus - Chen, Xiao Qiang; Liu, Jianquan; Wang, Tianyu; Zhao, Zhe; Li, Yongsheng; Cheng, Xiang Yu; Li, Wencui (Frontiers in Surgery, 2024)
Objective To investigate the short-term clinical efficacy of robot-assisted retrograde drilling and arthroscopic microfracture for osteochondral lesions of the talus (OCLT). Methods This study was divided into two groups: experimental group: robot-assisted retrograde drilling group; control group: arthroscopic microfracture group. A total of 6 OCLT patients who were treated with robot navigation-assisted retrograde drilling and 10 OCLT patients who were treated with arthroscopic microfracture between October 2020 and October 2021 were retrospectively analyzed. There were 11 males and five females, with a mean age of 36 years. The patients were followed up for 6–12 months to compare the changes in the OCLT lesion area by magnetic resonance imaging (MRI), visual analogue scale/score (VAS) and American Orthopedic Foot and Ankle Society score (AOFAS) before and after surgery. Results All 16 patients were followed up for an average of 8 months, and no complications such as joint infection, nerve injury, or active bleeding occurred during the follow-up period. Only one patient suffered discomfort involving transient postoperative pain in the operative area, but did not experience long-term numbness or chronic pain. Postoperative MRI revealed that none of the patients had severe signs of osteonecrosis, osteolysis or cystic changes of the talus, with lesion areas smaller than those before surgery. The difference was statistically significant (P < 0.01). The patients in the experimental group showed a more significant improvement in the last 3 months than in the first 3 months of the follow-up period. At the last follow-up, the VAS score was 3 points in the experimental group and 2.2 points in the control group, and the AOFAS score was 88.6 points in the experimental group and 88 points in the control group, all of which were significantly higher than those before operation, and the differences were statistically significant, but there was no statistically significant difference between the groups. Conclusion Both robot navigation-assisted retrograde drilling and arthroscopic microfracture for bone marrow stimulation (BMS) to treat OCLT in all patients obtained satisfactory effects in the short term. In addition, the follow-up revealed that with excellent efficacy and few complications, robot navigation-assisted retrograde drilling was safe and minimally invasive, and greatly reduced operative time. Consequently, robot navigation-assisted retrograde drilling for BMS was a safe and effective procedure for the treatment of OCLT.